INTERRELATION BETWEEN PROSTHETIC AND ORTHODONTIC TREATMENT - Diana Cerghizan; Neagu Anca Iulia; Marius Maris; Buruiana Daniela Laura; G.G. Condurache; Topor Gabriela; Mădălina Matei (Romanian Society of Oral Rehabilitation, 2020)
Prosthetic deal with methods of morphological-functional and aesthetic restoration of the maxillary (ADM) by means of biocompatible prostheses. The type of restored structures determines the delimitation of two distinct sub-domains: dental prosthetics and maxillofacial prosthetics; the first approaches the restoration of the dento-alveolar arches, and the second the prosthesis of other maxillofacial structures.. Orthodontics as a branch of dentistry has emerged as a way to correct dental malocclusions (poor alignment of teeth), but in contemporary society its goal has become to obtain an optimal position of facial soft tissues, so improving facial aesthetics while obtaining a functional occlusion (bites). Material and method: The paper presents an epidemiological study, conducted by clinical examination and observation sheets, of a representative group of 5 9 children aged 6-16 years, adolescents and young adults, which aimed to analyze the causes associated with the need for application prosthetic treatments in growing patients and establishing the frequency of prosthetic treatment necessary and performed at the level of permanent teeth. Results and discussions: There is a need to establish a prosthetic treatment for the growing patients, highlighting the consequences of non-prosthesis, as well as identifying treatment solutions targeted to each stage of age. Conclusions: Prosthetic treatments present in growing patients, satisfy a small proportion of their needs.